2021
DOI: 10.1152/jn.00602.2020
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue induces altered spatial myoelectric activation patterns in the medial gastrocnemius during locomotion

Abstract: Sustained voluntary muscle contractions can lead to fatigue, which diminishes the muscle's ability to absorb energy and produce force at a desired level. Prolonged fatigue can lead to a decline in human performance and increase the muscle's susceptibility to injury. In this study, we investigated how localized muscle fatigue affected spatial EMG patterns during locomotion. We recorded high-density electromyography (EMG) from the medial gastrocnemius of 11 healthy subjects while they walked (1.2 m/s) and ran (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Therefore, the decrease in the activity of the internal gastrocnemius muscle in the plyometric group can confirm the nervous fatigue caused by the plyometric training, which, as a result, reduces the use of muscle motor units [31]. Some other studies have shown the effect of fatigue on the decrease in muscle activity [32,33] which is associated with an increased chance of anterior cruciate ligament (ACL) injury [34]. The medial gastrocnemius muscle is one of the main muscles in the concentric phase for functional performance.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the decrease in the activity of the internal gastrocnemius muscle in the plyometric group can confirm the nervous fatigue caused by the plyometric training, which, as a result, reduces the use of muscle motor units [31]. Some other studies have shown the effect of fatigue on the decrease in muscle activity [32,33] which is associated with an increased chance of anterior cruciate ligament (ACL) injury [34]. The medial gastrocnemius muscle is one of the main muscles in the concentric phase for functional performance.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, for submaximal contraction, due to the decrease in force generation capacity during muscle fatigue, the increases in sEMG amplitude and energy were considered to reflect increased recruitment of additional motor units to maintain the strength level (Liu et al, 2003;Yang et al, 2009). Recently, Schlink et al (2021) observed that fatigue induces altered EMG activation patterns in the medial gastrocnemius. They confirmed that this may be a protective mechanism of the neuromuscular system to avoid muscle injury by distributing the muscle load more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…This can serve limiting the computation cost of normalization, which needs to be tested in new studies. However, prolonged walking has been shown to cause muscle fatigue ( Chambers et al, 2019 ) and consequently decreased sEMG amplitudes ( Schlink et al, 2021 ). More importantly, studies have shown variations in sEMG amplitudes with changes in walking speed ( den Otter et al, 2004 ), which may compromise accuracy of static reference values.…”
Section: Introductionmentioning
confidence: 99%